Adolescent engagement during assent for exome sequencing. Issue 4 (1st October 2016) - Werner-Lin, Allison; Tomlinson, Ashley; Miller, Victoria; Bernhardt, Barbara A.
ABSTRACT: Background : Research focused on describing the content of informed consent interactions has shed little light on how to best to encourage, support, and nurture adolescent participation in genomic sequencing. Research addressing adolescents' comprehension and agency is needed because sequencing may have significant implications for an adolescent's own future health status, as well as for other members of the adolescent's family. This article explores adolescent participation and decision making during informed consent for exome sequencing.Methods : Investigators recruited 25 adolescents with unexplained hearing loss, cardiac arrhythmias, mitochondrial disease, or neurodevelopmental disorders from an urban teaching and research hospital for participation in a research project offering whole exome sequencing. Twenty-five adolescents ages 12–19 years and their parents completed informed consent sessions with study clinicians lasting up to 90 minutes. Sessions were digitally recorded, transcribed, and analyzed using grounded theory's "constant comparative" method.Results : Adolescent participants were briefly active when asked direct questions. Otherwise, they stayed mostly quiet. Parents functioned as protectors and information holders. Clinicians used proscriptive language to direct families to consider adolescents' preferences, to balance the interests of multiple caregivers, and to give families time to consider their options before making decisions. In two cases of significant family disagreement, providers maintained a nondirective stance toward all parties and excused themselves from the intense discussion by deferring decisions to a later date.Conclusions : Conventional approaches to informed consent may be insufficient to the risks, benefits, and possibilities offered by genomic sequencing. Rather than target autonomy, enhancing the agency of adolescents in decision making may more appropriately address their needs so that all stakeholders provide input and are respected throughout the informed consent process.